Hubungan Status Gizi Dengan Asupan Zinc dan Kalsium Pada Remaja Usia 10-15 Tahun di Provinsi NTB NTT (Analisis Riskesdas 2010) - Fauziah, Faradhilla; Irianto, Sugeng Eko (Jurnal Nutrire Diaita (Ilmu Gizi), 2015)
AbstractBackground: Basic Health Research (RISKESDAS) data of 2010 shows that thinness prevalence of adolescents within 13-15 years old is 10.1 percent including 2.7 percent of very thin adolescents and obesity prevalence of 2.5 percent. Purpose: To understand the relationship of body mass index towards education level, intake of zinc and calcium to adolescents within 10-15 years old in West Nusa Tenggara and East Nusa Tenggara. Total respondents in this research are 1015 person, forming a sample of 2010’s Basic Health Research (Riset Kesehatan Dasar / RISKESDAS). Data collected in this research based on RISKESDAS report in 2010 on RKD10 block. RT and RKD10.OND block and interview method 1x24 hours. Result: The Average age of adolescents (12.28±1.725 SD), nutrition status is very skinny in West Nusa Tenggara in amount of 27 respondents (5.9%), skinny of 39 respondents (8.5%), normal of 331 respondents (72.4%), fat of 46 respondents (10.1%) and obese of 14 respondents (3.1%). Whereas in East Nusa Tenggara nutrition status of very skinny is 24 respondents (4.3%), skinny of 77 respondents (13.8%), normal of 417 respondents (74.7%), fat of 28 respondents (5.0%) and obese of 12 respondents (2.2%). The average of zinc intake in West Nusa Tenggara on male of age 10-12 and 13-15 years old (4.64±1.88 SD) and (5.34±2.1 SD), on female of age 10-12 and 13 – 15 years old (4.83±2.23 SD) and (4.96±2.24 SD), in East Nusa Tenggara on male of age 10-12 and 13-15 years old (3.42±1.82 SD) and (3.77±1.79 SD), on female of age 10-12 and 13 – 15 years old (3.64±1.99 SD) and (4.17±2.98 SD). There is no relationship between nutrition status with age and zinc intake (p>0.05). There is no difference between nutrition status and education level, nor between sex with zinc intake and calcium. There is a difference between nutrition status with sex and there is also a difference between nutrition status with intake of calcium (p<0.05). Conclusion: Information and socialization about balance nutrition and nutrition status towards adolescents is required. Keywords: body mass index, zinc, calcium